Teori Penawaran dan Market Balancing dalam Perspektif Ekonomi Islam: Tinjauan Terhadap Justice Principlies, Maslahah, dan Mekanisme Pasar Islami - Ahmad Sukron; Rahma Hafsah Ramadhan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This research is studies about modern economic growth by their problem. The rapid growth of the modern economy has been accompanied by various challenges in market activities, including monopoly, hoarding (ihtikar), and price manipulation, all of which can disturb market equilibrium. Within the framework of Islamic economics, market operations are not merely directed toward maximizing profits but are also expected to uphold the principles of justice ('adl) and maslahah (public welfare). Consequently, the study of supply theory and market equilibrium becomes important for understanding how Islamic principles are implemented in economic practices. This research seeks to examine supply theory and market equilibrium from the perspective of Islamic economics by focusing on the principles of justice, maslahah, and the Islamic market mechanism. The study adopted a qualitative approach using library research methods. The data were obtained from academic books, scientific journals, and other relevant scholarly references and were analyzed through content analysis. The results indicate that supply in Islamic economics is determined not only by price and production costs but also by Islamic ethical values that shape producers' decisions. The principle of justice promotes transparent and honest transactions, whereas the principle of maslahah ensures that economic activities generate wider social benefits. In addition, the economic thoughts of Al-Ghazali, Ibn Taymiyyah, and Ibn Khaldun highlight the significance of establishing a market mechanism that is free from monopoly, price manipulation, and hoarding in order to maintain a fair market equilibrium. These findings suggest that applying the principles of justice and maslahah within the supply mechanism can support the creation of a market system that is more balanced, sustainable, and oriented toward public welfare.